MEDICAL, PSYCHOLOGICAL, AND LEGAL FOUNDATIONS OF PREPARING YOUTH FOR FAMILY LIFE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article provides detailed information on preparing young people for family life, the negative consequences of early marriage, and the medical, psychological, and legal foundations for strengthening the family. The presented material, from problem statement to its solution, leaves a positive impression on the reader and helps foster a deep understanding of the topic.